Hubungan Body Image dengan Perilaku Self Esteem pada Remaja Putri - Idris, Indrayani; Suhermi; Alam, Rizqy Iftitah; Wan Sulastri Emin (Window of Nursing Journal, 2024)
Adolescents will go through various changes in themselves both physically, emotionally and psychologically. Associated with the physical changes that occur, adolescents must be able to accept their physical condition and use their bodies effectively. Physical changes that occur in adolescents are related to body image. A teenager is said to have a positive body image if he is satisfied with his current physical condition. This study aims to determine the relationship between body image and self-esteem behavior in young women in Punranga Village. This type of research is quantitative with a cross sectional study approach. The sampling technique used purposive sampling technique as many as 66 people from a total population of 80 people and used an instrument in the form of a questionnaire to retrieve information. The analysis uses the Chi-Square test as a tool to test the relationship between variables with a significance level of = 0.05. The results obtained 23 respondents who have a negative body image, of which there are 3 respondents (13.0%) who have low self-esteem and 20 respondents (87.0%) who have high self-esteem behavior. As for the positive body image, there are 43 respondents, of which 17 respondents (39.5%) have low self-esteem behavior and 26 respondents (60.5%) have high self-esteem behavior. The results of statistical tests with Chi-Square obtained p = 0.026 (<0.05). The conclusion in this study is that there is a relationship between body image and self-esteem in young women in Punranga Village. For this reason, it is hoped that adolescents will always increase their self-confidence and respect themselves, both in appearance and physically.